2010
DOI: 10.17955/tvr.110.3.616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Auditory-Verbal Therapy for School-Aged Children with Hearing Loss: An Exploratory Study

Abstract: A longitudinal study reported positive speech and language outcomes for 29 children with hearing loss in an auditory-verbal therapy program (AVT group) (aged 2 to 6 years at start; mean PTA 79.39 dB HL) compared with a matched control group with typical hearing (TH group) at 9, 21, and 38 months after the start of the study. The current study investigates outcomes over 50 months for 19 of the original pairs of children matched for language age, receptive vocabulary, gender, and socioeconomic status. An assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…Hearing impaired children, whether using hearing aids or CI, show rates of improvement on standardized measures of language that outpace what would be expected through normal development (Rhoades and Chisolm, 2001; Hogan et al, 2008, p. 2), though the multi-year duration of AVT, and the lack of a control group make it difficult to be certain if it is the therapy, and not development, that is driving the change (Eriks-Brophy, 2004; Rhoades, 2006). Recently, a more controlled study on AVT found significant improvements on receptive language, phonological awareness, articulation, and speech-in-noise perception (Fairgray et al, 2010). Again, the small sample size limits generalizability, but the significant improvement relative to baseline in a controlled setting suggests that AVT, or auditory training, could be effective for improving speech-and-language outcomes for CI recipients.…”
Section: Auditory and Speech Perceptual Trainingmentioning
confidence: 99%
“…Hearing impaired children, whether using hearing aids or CI, show rates of improvement on standardized measures of language that outpace what would be expected through normal development (Rhoades and Chisolm, 2001; Hogan et al, 2008, p. 2), though the multi-year duration of AVT, and the lack of a control group make it difficult to be certain if it is the therapy, and not development, that is driving the change (Eriks-Brophy, 2004; Rhoades, 2006). Recently, a more controlled study on AVT found significant improvements on receptive language, phonological awareness, articulation, and speech-in-noise perception (Fairgray et al, 2010). Again, the small sample size limits generalizability, but the significant improvement relative to baseline in a controlled setting suggests that AVT, or auditory training, could be effective for improving speech-and-language outcomes for CI recipients.…”
Section: Auditory and Speech Perceptual Trainingmentioning
confidence: 99%
“…The aim of habilitation programs is for children with HL to function similarly as their hearing peers. Recent advancements in cochlear implant technology have conveyed research interest in auditory-driven approaches for HL children, such as auditory–verbal therapy (AVT) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it shows that not just in the initial years, AVT is required but also during the later stages, that is, during school age. Therefore, it shows that continuous AVT/Rehabilitation is required for better performance [35].…”
Section: Importance Of Auditory-verbal Therapymentioning
confidence: 99%